DIGITAL APPROACH TO TEACH CREATIVE WRITING WITH SECONDARY STUDENT LEARNERS OF ENGLISH - Rocha, Ana Paula; Casanova, Maria Prazeres (LLT Journal: A Journal on Language and Language Teaching, 2023)
In this article, we share our reflections and analysis on the potential of digital resources in teaching creative writing in English and promoting the learning of a foreign language in a collaborative environment. Our work aims to identify best practices in using digital tools such as Google Workspace, Padlet, and Issuu, for in-class activities with seventy secondary students. We conducted a study following an action-research methodology in the classroom and applied digital teaching strategies with learners of a second language. The focus was on a creative and collaborative writing process, to develop imagination in the conception of fictional stories while promoting collaborative skills. Our key question was "What are the digital pedagogical strategies that can contribute to the creative and collaborative writing competence in a foreign language with secondary school students?" We were interested in examining the potential of a writing collaborative activity in a digital environment as a stimulus to learn the linguistic rules and expand the vocabulary. Additionally, we analyzed the results of the assessment executed among peers, applying selected rubrics for the competencies of cooperation and participation. As a result, we found that the students had reached a higher level of reflection towards texts.